2000
DOI: 10.1155/np.2000.19
|View full text |Cite
|
Sign up to set email alerts
|

GABA and Muscimol as Reversible Inactivation Tools in Learning and Memory

Abstract: Reversible inactivation of brain areas is a useful method for inferring brain-behavior relationships. Infusion of GABA or of the GABA receptor agonist muscimol is considered one interesting reversible inactivation method because it may not affect fibers of passage and may therefore be compared to axon-sparing types of lesions. This article reviews the data obtained with this method in learning and memory experiments. A critical analysis of data, collected in collaboration with Simon Brailowsky, with chronic GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 74 publications
1
32
0
Order By: Relevance
“…As outlined in the Introduction, temporary regional brain inactivation may reveal some regional functions that have eluded lesion studies (Majchrzak and Di Scala 2000). Permanent brain lesions may fail to reveal normal behavioral contributions of the lesioned regions, because, following complete and permanent loss of hippocampal output, other brain regions may mediate these processes or because deficits could be masked by lesioninduced distal changes (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined in the Introduction, temporary regional brain inactivation may reveal some regional functions that have eluded lesion studies (Majchrzak and Di Scala 2000). Permanent brain lesions may fail to reveal normal behavioral contributions of the lesioned regions, because, following complete and permanent loss of hippocampal output, other brain regions may mediate these processes or because deficits could be masked by lesioninduced distal changes (cf.…”
Section: Discussionmentioning
confidence: 99%
“…We used microinfusion of the GABA A receptor agonist, muscimol (Majchrzak and Di Scala, 2000), to explore the effect of reversible neuronal inactivation of the ACgx on the encoding and retrieval/expression of recognition memory. In a series of four experiments, effects on encoding versus retrieval/expression were examined after both short (20 min) retention delays similar to those used in previous lesion studies and a longer (24 h) delay more similar to those used in the electrophysiological studies which have indicated a role for ACgx in NOR.…”
Section: United Kingdommentioning
confidence: 99%
“…Cells that are hyperpolarized by muscimol are less likely to fire action potentials and remain in that inactivated state until the drug is no longer effective (Majchrzak and Di Scala 2000). Muscimol binds with the GABA A receptor, which allows chloride ions to enter the cell, effectively decreasing neural activity beginning 30 min after infusion with the effect lasting at least 2 h post-infusion (Martin 1991).…”
Section: Muscimol Infusion Proceduresmentioning
confidence: 99%
“…It is possible that the discrepancy between these earlier studies and the present data are due in part to differential effects of lesions and temporary inactivation. Although excitotoxic lesions preserve fibers of passage, cell bodies are extensively damaged (Zapeda et al, 2012), and it is likely that the surviving neurons which surround the damaged area function differently after the lesion (Majchrzak & Di Scala, 2000). Furthermore, several studies have indicated that functional recovery can occur following lesions in general (Casamenti et al, 1988;Gardiner et al, 1987;Wenk & Olton, 1984) and focal lesions of the hippocampus in particular (Zapeda et al, 2012).…”
Section: Histologymentioning
confidence: 99%